2018
DOI: 10.3390/rs11010040
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Precise Orbit Predictions for a HY-2A Satellite with Three Atmospheric Density Models Based on Dynamic Method

Abstract: HY-2A (Haiyang 2A) is the first altimetry satellite in China, and it was designed to be in a repeated ground track orbit to achieve the mission targets. Maneuvers are necessary to keep the satellite on the designed orbit according to the dynamic precise orbital prediction. Atmospheric density models are essential for predicting the low Earth orbit (LEO) satellites, such as HY-2A. Nevertheless, it is a complex process to determine the optimal atmospheric density model for orbit prediction. In this paper, short-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…[5,6]. Nowadays, this system can determine the orbits of the LEO satellites at a precision level of 1-2 cm, and has been applied in the establishment of ITRF2005, ITRF2008, and ITRF2014 [7][8][9][10][11][12]. Gambis [5] analyzed the short-term PM series calculated by DORIS and found that differences in PM solved by DORIS and that by IERS C04 were 1.13 mas and 0.69 mas, in the X and Y directions, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6]. Nowadays, this system can determine the orbits of the LEO satellites at a precision level of 1-2 cm, and has been applied in the establishment of ITRF2005, ITRF2008, and ITRF2014 [7][8][9][10][11][12]. Gambis [5] analyzed the short-term PM series calculated by DORIS and found that differences in PM solved by DORIS and that by IERS C04 were 1.13 mas and 0.69 mas, in the X and Y directions, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…An example, for the diagnose of such problems (anomalies), of the first nature, for LEO satellites are analyzes by using electron data from the Medium Energy Proton and Electron Detector onboard the National Oceanic and Atmospheric Administration (NOAA-15) satellite [10]. Not only technical issues impact the satellite's operation, but also different environment orbit perturbations which are mainly caused by atmospheric drag and non-homogeneity of the Earth's mass, which belong under the second nature [11]. Among these perturbations is the perigee deviation, what is analyzed in this paper specifically for the case of the Sun Synchronized orbits.…”
Section: Introductionmentioning
confidence: 99%